COMMUNI.CARE (COMMUNIcation and Patient Engagement at Diagnosis of PAncreatic CAncer): Study Protocol - Consolandi, Monica; Martini, Carlo; Reni, Michele; Arcidiacono, Paolo Giorgio; Falconi, Massimo; Graffigna, Guendalina; Capurso, Gabriele (Frontiers in Medicine, 2020)
Background: In many cases of pancreatic adenocarcinoma (PDAC), the diagnosis comes as a surprise to the patient, who often faces a disease that is already at an advanced stage, with poor prognosis. The clinical visit during which the diagnosis is communicated together with the first information regarding the planned treatments is of paramount importance. We hypothesize that the clarity of such information can influence patients' engagement and thus their level of compliance. Aims: This study aims to collect (a) quantitative data on the level of PDAC patient engagement, (b) data on the rate of understanding of the information received from the doctor, and (c) data on level of compliance; the possible associations between these variables will be analyzed. Methods: This is a single-center, observational, cross-sectional cohort study on patients diagnosed with PDAC, approved by the Ethics Committee of the San Raffaele Hospital. As no preliminary data are available on the association between PDAC patients' understanding rate and their level of engagement and of compliance, no power calculation is possible. This is a pilot study, aimed at enrolling at least 45 PDAC patients during a period of 3 months. Conclusion: COMMUNIcation and Patient Engagement at Diagnosis of PAncreatic CAncer (COMMUNI. CARE) will be the first study specifically investigating whether there is a relation between PDAC patients' engagement, rate of understanding at the time of diagnosis, and compliance.